1967
DOI: 10.1021/jf60149a016
|View full text |Cite
|
Sign up to set email alerts
|

UPTAKE OF INSECTICIDES.Investipationrs on Dursban Insecticide. Uptake and Translocation of ["Cq O,O,-DiethylO-3,5,6-Trichloro-i-pyridyl Phosphoro-thioate and ["C] O,O-Diethyl 0-3,5,6-Trichloro-2-pyridyl Phosphorothioate by Beans and Corn

Abstract: The uptake and translocation of [36C1] Dursban and [14C] Dursban by leaves and corn plants were studied. Both root and leaf absorption were insignificant. Only a small percentage of the radioactivity (1 to 2%) was translocated into the plant. These were largely breakdown products such as the 3,5,6-trichloro-2-pyridinol.In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In general, it has been shown that negligible levels of CPS enter the plant via the roots, indicating its non-systemic nature. However, most studies have focused on CPS uptake by plants in soil (Smith et al 1967a; Bauriedel et al 1976; Bauriedel and Miller 1986a, 1986b), and the results were similar (i.e., negligible uptake) to the results obtained in nutrient solution (Smith and Watson 1964). While previous study have shown its uptake by plants to be insignificant, our results show that significant amounts of CPS were taken up from the nutrient solution by woody plants, poplar and willow.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In general, it has been shown that negligible levels of CPS enter the plant via the roots, indicating its non-systemic nature. However, most studies have focused on CPS uptake by plants in soil (Smith et al 1967a; Bauriedel et al 1976; Bauriedel and Miller 1986a, 1986b), and the results were similar (i.e., negligible uptake) to the results obtained in nutrient solution (Smith and Watson 1964). While previous study have shown its uptake by plants to be insignificant, our results show that significant amounts of CPS were taken up from the nutrient solution by woody plants, poplar and willow.…”
Section: Discussionmentioning
confidence: 58%
“…Removal of CPS by plants is based on the ability of plants to take up CPS into tissues and to degrade it. Although the fate of CPS has been documented in the environment, little is known about the fate of this contaminant and its metabolites within a plant system (Smith et al 1967a, 1967b; Rouchaud et al 1991). In addition, most plant species that have been tested so far for CPS uptake are herbaceous plants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, SMITH et al (1967) found that uptake of 36CI_ and 14C_ labeled Dursban® following topical or spray application to leaves of several plant species was insignifIcant, amounting to one to two percent. This insecticide has a water solubility of only about two p.p.m.…”
Section: Properties Of the Pesticide Formulation As Related To Rmentioning
confidence: 99%
“…Of six known biodegradable surfactants, he found five to be toxic at one percent. It is of interest that SMITH et al (1967), working with four new biodegradable surfactants, noted that they were inherently phytotoxic but gave excellent visual wetting of maize foliage. As to enhancing the herbicidal activity of amitrole, dalapon, and paraquat, they proved to be equal or superior to some of the standard surfactants in common use.…”
Section: Properties Of the Pesticide Formulation As Related To Rmentioning
confidence: 99%
“…This is convenient, for example, with combinations of any two of the three radiolabels, H8, Cl4, and P82, or by the use of separate but identical experiments either with C 14 samples separately labeled at different positions in the molecule or with C14 and 8 85 or C14 and Cl36 samples. This procedure has been particularly useful with carbamates, involving carbonyl, N-methyl, and ring or ring-substituent labels (CASIDA 1963, DOROUGH and CASIDA 1964, DOROUGH et al 1963, KRISHNA and CASIDA 1966, KUHR and CASIDA 1967, LEELING and CASIDA 1966, OONNlTHAN and CASIDA 1966, with pyrethroids separately labeled in the acid and alcohol moieties (YAMAMOTO andCASIDA 1966, YAMA-MOTO et al 1968), with organophosphates labeled at the phosphorus, O-alkyl and/or phenolic or enolic moiety positions (BERENDS et al 1959, HODGSON and CASIDA 1962, MENZER and CASIDA 1965, ROGER et al 1964, SMITH et al 1967, STIASNI et al 1967, and with methylenedioxyphenyl synergists labeled in a ring-substituent position in addition to the methylene-C14-dioxy moiety a, ESAAC et al 1968, KUWATSUKA and CASIDA 1965, SCHMIDT and DAHM 1956). …”
Section: Selection Of Site For Labelingmentioning
confidence: 99%